2013
DOI: 10.1177/2045125313476877
|View full text |Cite
|
Sign up to set email alerts
|

Continuing clozapine with granulocyte colony-stimulating factor in patients with neutropenia

Abstract: Background: The current guidelines dictate that clozapine should be stopped following the emergence of neutropenia. Various alternative approaches have been tried in the past, among them one rarely used alternative being to continue treatment with clozapine with coprescription of granulocyte colony-stimulating factor (G-CSF). Aim and method: In this case series we aim to describe the treatment and progress of a number of patients in a secure psychiatric hospital in the UK. These patients were restarted on cloz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Of the articles identified, the majority were case reports with the other article types consisting of five case series (Hagg et al, 2003;Joffe et al, 2009;Khan et al, 2013;Mathewson and Lindenmayer, 2007;Sengupta and Harvey, 2010) and one cohort study where individual cases were reported (Meyer et al, 2015). The majority of cases were male (82%), Caucasian (67%) and young (median age 34 years, range 17-63).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the articles identified, the majority were case reports with the other article types consisting of five case series (Hagg et al, 2003;Joffe et al, 2009;Khan et al, 2013;Mathewson and Lindenmayer, 2007;Sengupta and Harvey, 2010) and one cohort study where individual cases were reported (Meyer et al, 2015). The majority of cases were male (82%), Caucasian (67%) and young (median age 34 years, range 17-63).…”
Section: Resultsmentioning
confidence: 99%
“…The absence of specific side effects attributable to G-CSF was reported in 15 cases. Most adverse outcomes were related to recurrent neutropenia with an episode of severe sepsis due to tonsillitis reported in one case (Joffe et al, 2009), pneumonia reported in another case (Khan et al, 2013) and complicated urinary tract infection in another (Majczenko and Stewart, 2008). Mild euphoria was reported in one case (Broughton et al, 2012) shortly after each weekly dose of lenograstim 105 µg.…”
Section: Safety Outcomesmentioning
confidence: 99%
“…We identified 32 episodes(in 31 patients) of clozapine re-challenge, where G-CSF was prescribed as maintenance prophylaxis (n=23)(9-19) or as single, as required administrations (n=9) (13,14,(20)(21)(22)(23)(24) to enable continued clozapine treatment.…”
Section: Study Selection Study and Participant Characteristicsmentioning
confidence: 99%
“…The combined use clozapine and lithium may increase the risk of neurotoxic reactions (Bender et al, 2004) while there is a paucity of data on the use of G-CSF in preventing clozapine-associated haematological adverse effects (Lally et al, 2017). Long-term G-CSF adverse effects can include enlarged spleen, hepatomegaly, urinary abnormalities and very rarely, splenic rupture (Khan et al, 2013). It could be argued that with the lowering of the threshold using the US criteria, such remedial strategies could become unnecessary in most instances.…”
Section: Discussionmentioning
confidence: 99%